Epitaxial Growth of Lead‐Free 2D Cs3Cu2I5 Perovskites for High‐Performance UV Photodetectors. Issue 27 (31st May 2022) - Lv, Jianan; Lu, Xinyue; Li, Xin; Xu, Minxuan; Zhong, Jiasong; Zheng, Xin; Shi, Yueqin; Zhang, Xuefeng; Zhang, Qi
Abstract: The all‐inorganic lead‐free Cu‐based halide perovskites represented by the Cs−Cu−I system, have sparked extensive interest recently due to their impressive photophysical characteristics. However, successive works on their potential application in light emission diodes and photodetectors rely on tiny polycrystals, in which the grain boundaries and defects may lead to the performance degradation of their embodied devices. Here, 2D all‐inorganic perovskite Cs3 Cu2 I5 single crystals are epitaxially grown on mica substrates, with a thickness down to 10 nm. The strong blue emission of the Cs3 Cu2 I5 flakes may originate from the radiative transition of self‐trapped excitons associated with a large Stocks shift and long (microsecond) decay time. Ultravioelt (UV) photodetectors based on individual Cs3 Cu2 I5 nanosheets are fabricated via a swift and etching‐free dry transfer approach, which reveal a high responsivity of 3.78 A W –1 (270 nm, 5 V bias), as well as a fast response speed (τrise ≈163 ms, τdecay ≈203 ms), outperforming congeneric UV sensors based on other 2D metal halide perovskites. This work therefore sheds light on the fabrication of green optoelectronic devices based on lead‐free 2D perovskites, vital for the sustainable development of photoelectric technology. Abstract : This article reports the epitaxial growth of lead‐free 2D Cs3 Cu2 I5 perovskites, where the strong blue emission with a large Stocks shift and long (microsecond) lifetime is attributed to a radiative transition of self‐trapped excitons. The Cs3 Cu2 I5 photodetector reveals a high responsivity of 3.78 A W –1 (270 nm, 5 V) with a fast characteristic (τrise /τdecay ≈ 163/203 ms), outperforming congeneric UV sensors.